2022
DOI: 10.3390/antibiotics11081007
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime/Avibactam in Ventilator-Associated Pneumonia Due to Difficult-to-Treat Non-Fermenter Gram-Negative Bacteria in COVID-19 Patients: A Case Series and Review of the Literature

Abstract: Ventilator-associated pneumonia (VAP) in critically ill patients with COVID-19 represents a very huge global threat due to a higher incidence rate compared to non-COVID-19 patients and almost 50% of the 30-day mortality rate. Pseudomonas aeruginosa was the first pathogen involved but uncommon non-fermenter gram-negative organisms such as Burkholderia cepacea and Stenotrophomonas maltophilia have emerged as other potential etiological causes. Against carbapenem-resistant gram-negative microorganisms, Ceftazidim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…In fact, we had the chance to identify both Gram-positive and Gram-negative cocci and rods, including staphylococci, Bacillus spp., Enterobacterales, and non-fermentative Gram-negative bacilli. Most of them can be opportunistic pathogens responsible for severe infections, such as respiratory tract and bloodstream infections, mainly in immunocompromised patients or in the presence of invasive medical devices [ 20 , 21 ]. Moreover, in healthcare settings, most of these bacteria show alarming patterns of antimicrobial resistance, with high morbidity and mortality rates and poor therapeutic options [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we had the chance to identify both Gram-positive and Gram-negative cocci and rods, including staphylococci, Bacillus spp., Enterobacterales, and non-fermentative Gram-negative bacilli. Most of them can be opportunistic pathogens responsible for severe infections, such as respiratory tract and bloodstream infections, mainly in immunocompromised patients or in the presence of invasive medical devices [ 20 , 21 ]. Moreover, in healthcare settings, most of these bacteria show alarming patterns of antimicrobial resistance, with high morbidity and mortality rates and poor therapeutic options [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of post hoc predicted exposures for adults from the phase III program showed that in multiple subgroups of patients with markers of severe/critical illness, including APACHE II score > 10, systemic inflammatory response syndrome, bacteremia, fever, and augmented renal CL, approved adult doses achieved joint target attainment > 90% 5 . In addition, several real‐world studies have reported positive outcomes for the recommended ceftazidime‐avibactam doses in critically ill adult patients 33–35 . Our modeling approach and the resulting dose recommendations based on matching exposures for pediatric patients (including renal impairment) with adults suggests that the recommended pediatric doses will also be suitable for critically ill children.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, several real-world studies have reported positive outcomes for the recommended ceftazidime-avibactam doses in critically ill adult patients. [33][34][35] Our modeling approach and the resulting dose recommendations based on matching exposures for pediatric patients (including renal impairment) with adults suggests that the recommended pediatric doses will also be suitable for critically ill children.…”
Section: Articlementioning
confidence: 99%
“…Diverse new agents active against certain CR pathogens, including ceftazidime-avibactam [ 125 ], ceftolozane-tazobactam [ 126 , 127 ], piperacillin-tazobactam [ 128 ], meropenem-vaborbactam [ 129 ], imipenem-relebactam [ 130 ], imipenem-cilastatin-relebactam [ 131 ] are used in clinics. Specifically, plazomicin [ 132 ], eravacycline [ 133 ], and cefiderocol [ 134 ] have been approved for clinical use or are reaching late-stage clinical development [ 135 ].…”
Section: Therapies For Antibiotic-resistant Bacteriamentioning
confidence: 99%